Integrasi Pendidikan Karakter Berbasis Al-Qur’an dalam Pembelajaran Tematik di MI Ma'arif Sutawinangun Kabupaten Cirebon - Sya'roni, Mohamad Mizan; Nurhasan, Arief Muhammad (LJPI UI Bunga Bangsa Cirebon, 2022)
The moral crisis among Indonesian students has become a serious challenge that requires a comprehensive solution through character education based on religious values. This study aims to examine the integration of Qur'anic values in forming students' moral knowing, moral feeling, and moral action in thematic learning at MI Ma'arif Sutawinangun, Cirebon Regency, using Thomas Lickona's theoretical perspective. The research employs a qualitative approach with a descriptive case study design. Primary data were obtained from five informants selected through purposive sampling technique, including the school principal, vice principal for curriculum, two classroom teachers, and one Al-Qur'an Hadith subject teacher. Data collection techniques used methodological triangulation combining participatory observation, in-depth interviews, and documentation study. Data analysis used the interactive model of Miles, Huberman, and Saldaña. The results indicate that the integration of Qur'anic values in thematic learning is implemented holistically through contextual learning strategies, habituation of religious practices, and applicative programs that simultaneously address the three dimensions of character. Moral knowing formation is conducted through integrative learning and value discussions, moral feeling is developed through worship habituation and self-reflection, while moral action is realized through practical activities and a sustainable positive behavior reinforcement system.